EHS and AHS guidelines for treatment of primary ventral hernias in rare locations or special circumstances. Issue 2 (9th January 2020) - Henriksen, N. A.; Kaufmann, R.; Simons, M. P.; Berrevoet, F.; East, B.; Fischer, J.; Hope, W.; Klassen, D.; Lorenz, R.; Renard, Y.; Garcia Urena, M. A.; Montgomery, A.; et al.
Abstract : Background: Rare locations of hernias, as well as primary ventral hernias under certain circumstances (cirrhosis, dialysis, rectus diastasis, subsequent pregnancy), might be technically challenging. The aim was to identify situations where the treatment strategy might deviate from routine management. Methods: The guideline group consisted of surgeons from the European and Americas Hernia Societies. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used in formulating the recommendations. The Scottish Intercollegiate Guidelines Network (SIGN) critical appraisal checklists were used to evaluate the quality of full‐text papers. A systematic literature search was performed on 1 May 2018 and updated 1 February 2019. The Appraisal of Guidelines for Research and Evaluation (AGREE) instrument was followed. Results: Literature was limited in quantity and quality. A majority of the recommendations were graded as weak, based on low quality of evidence. In patients with cirrhosis or on dialysis, a preperitoneal mesh repair is suggested. Subsequent pregnancy is a risk factor for recurrence. Repair should be postponed until after the last pregnancy. For patients with a concomitant rectus diastasis or those with a Spigelian or lumbar hernia, no recommendation could be made for treatment strategy owing to lack of evidence. Conclusion: This is the first European and American guideline on the treatment of umbilical and epigastric hernias in patients with special conditions, including Spigelian and lumbar hernias. All recommendations were weak owing to a lack of evidence. Further studies are needed on patients with rectus diastasis, Spigelian and lumbar hernias. Abstract : This guideline addresses the treatment of umbilical and epigastric hernias in clinically challenging situations (cirrhosis, dialysis, subsequent pregnancy, rectus diastasis), as well as the treatment of Spigelian and primary lumbar hernias. Emphasises the need for better evidence Abstract : Antecedentes: Las hernias de localización rara, así como las hernias ventrales primarias en determinadas circunstancias (cirrosis, diálisis, diástasis de recto, tras un embarazo) pueden ser complejas desde el punto de vista técnico. El objetivo fue identificar situaciones en las que la estrategia de tratamiento pudiera ser diferente del tratamiento habitual. Métodos: Esta guía fue elaborada por cirujanos de las sociedades europeas y americana de hernia ( European Hernia Society, EHS y American Hernia Society, AHS). La búsqueda sistemática de la literatura se efectuó el 1 de mayo de 2018 y se actualizó el 1 de febrero de 2019. Para evaluar la calidad de los artículos completos seleccionados se utilizó la normativa SIGN ( Scottish Intercollegiate Guidelines Network ). Las recomendaciones formuladas siguieron la metodología GRADE ( Grading of Recommendations Assessment, Development and Evaluation ) y la redacción de la guía siguió las normas AGREE ( Appraisal of Guidelines for Research & Evaluation ). Resultados: La literatura es limitada en cantidad y calidad. La mayoría de las recomendaciones se calificaron como débiles en función de la baja calidad de la evidencia. En pacientes con cirrosis o en diálisis, se sugiere una reparación con malla preperitoneal. Un embarazo tras la reparación de una hernia es un factor de riesgo de recidiva. La reparación debería posponerse hasta después del último embarazo. Debido a la falta de evidencia no se pudo hacer ninguna recomendación para la reparación de hernias en pacientes con diástasis de recto concomitante o con hernias de Spigel o lumbares. Conclusión: Esta es la primera guía europea y americana del tratamiento de hernias umbilicales y epigástricas en pacientes con patologías especiales, incluyendo las hernias de Spigel y lumbares. Todas las recomendaciones fueron débiles debido a la falta de evidencia. Se necesitan más estudios en pacientes con diástasis de recto, hernias de Spigel y lumbares.